LA EFICIENCIA ECONÓMICA DE LA LEY PENAL - Eiranova Encinas, Emilio (REVISTA PROCESOS DE MERCADO, 2022)
This work examines the efficiency of the criminal law. To do this, the author designs a model in which the economic variables that affect the efficiency of the penal system are taken into account. The author also explains the way in which a regulatory intervention by the State provides a deceptive feeling of security. As it also uses the criminal rules to release the workload ofcourts. In the process of seeking criminal efficiency through regulatory intervention, a spiral of inefficiency is generated and situations are caused to which unfair solutions are applied. As a consequence, the liberal principles that inspired criminal law are vanishing. This study represents a radical change from the point of view of criminal dogmatics.